The formula : how algorithms solve all our problems --and create more - Dormehl, Luke (New York, New York : Penguin Group (USA) LLC, 2014)
In The Formula, Luke Dormehl takes readers inside the world of numbers, asking how we came to believe in the all-conquering power of algorithms; introducing the mathematicians, artificial intelligence experts and Silicon Valley entrepreneurs who are shaping this brave new world, and ultimately asking how we survive in an era where numbers can sometimes seem to create as many problems as they solve.
An explanation of the title, and other cyberbole -- The quantified selves -- The match & the spark -- Do algorithms dream of electric laws? -- The machine that made art -- Predicting the future.
'A Perigee book.'
'Previously published in the UK in 2014 by Virgin Books, an imprint of Ebury Publishing'--Title-page verso.
Includes bibliographical references : pages [245]-266 and index.
Keywords: Algorithms -- Popular works; Algorithms -- History